Cost-effectiveness analysis of three surgical approaches for parathyroidectomy in secondary hyperparathyroidism patients - Sa, Qila; Zhou, Yinghui; Cheng, Guangming; Nan, Boyuan; Feng, Yingnan; Zhang, Ningyuan; Xie, Wantao; Zhang, Wei (Frontiers in Endocrinology, 2025)
BackgroundThere are three main surgical treatment options for secondary hyperparathyroidism (SHPT): subtotal parathyroidectomy (sPTX), total parathyroidectomy with auto-transplantation (tPTX+AT), and total parathyroidectomy (tPTX). However, a debate regarding which of these surgical methods is optimal has been ongoing. Aim of this study is to compare medical costs and final outcomes associated with the three surgical approaches for the entire treatment duration, aiming to identify the most cost-effective surgical method.MethodsBased on previous research data from domestic and international studies, as well as data from on-site surveys, TreeAge Pro 2022 software was used to construct a Markov model for the surgical treatment of SHPT patients. The model was run using data from the 2022 registered population of end-stage renal disease dialysis patients in China (1 million) as baseline cohort. Main indicators for this analysis are total cost, quality-adjusted life years, and incremental cost-effectiveness ratio (ICER). The study period is 10 years post-surgery, with a discount rate of 5% per year. Uncertainty in the model was assessed using one-way sensitivity analysis and probabilistic sensitivity analysis (PSA).ResultsThe costs incurred by SHPT patients undergoing sPTX, tPTX, and tPTX+AT within 10 years post-surgery are 7042.54, 9983.00, and 11435.60, respectively, with total utilities generated being 13.23 QALYs, 18.76 QALYs, and 18.69 QALYs. Compared to sPTX, the incremental costs and incremental effects of tPTX and tPTX+AT are 2,924.71 and 4,456.66, with 5.53 QALYs and 5.46 QALYs, respectively. The ICER for tPTX and tPTX+AT groups are 532.13/QALY and 805.10/QALY, respectively, which are well below our set willingness-to-pay (WTP) threshold. Sensitivity analysis results indicate that varying any parameter within a certain range over the given time interval will not cause the ICER to exceed the WTP threshold and will not reverse the primary analysis results.ConclusionIn the Chinese healthcare system, tPTX is considered the most cost-effective treatment for refractory hyperparathyroidism, when compared to tPTX+AT and sPTX.